The Motherhood Wage Penalty & Grandparent Provided Childcare in Australia - Payten, D (My University, 2014)
Does affordable, quality childcare or paid parental leave lead to improved labour market outcomes for women re-entering the workforce post-childbirth?
Honours Dissertation - University of Western Australia
Keywords: Child Care; Ageing -- Grandparents; Income & Finance; Families -- Mothers; Ageing; Families and relationships; Income, wealth and finances; Ageing; Families; Child Care; Income & Finance; Grandparents; Mothers; Families and relationships; Ageing; Income, wealth and finances